Treatment of recalcitrant wastewater and hydrogen production via microbial electrolysis cells - Shen, Ruixia; Zhao, Lixin; Lu, Jianwen; Watson, Jamison; Si, Buchun; Chen, Xi; Meng, Haibo; Yao, Zonglu; Feng, Jing; Liu, Zhidan (International Journal of Agricultural and Biological Engineering, 2019)
A large amount of real complex wastewaters are generated every year, which leads to a great environmental burden. Various treatment technologies were deployed to remove the contaminants in the wastewaters. However, these actual wastewaters have not been sufficiently treated due to their complex properties, high-concentration organics, incomplete utilization of hard-biodegradable substrates, the high energy input required, etc. Recently, microbial electrolysis cells (MECs), a great potential technology, has emerged for various wastewater treatment, because not only do they demonstrate satisfactory performance during wastewater treatment, but they also generate renewable H2 as a clean energy carrier. Unlike previous reviews, this review introduced the characteristics of every complicated wastewater, and focused on analyzing and summarizing MEC development for wastewater treatment. The performances of MECs were systematically reviewed in terms of organics removal, H2 production, Columbic efficiency, and energy efficiency. MEC performances for treating actual complex wastewaters and producing H2 can be optimized through operation parameters, electrode materials, catalyst materials, etc. In addition, the challenges and opportunities including complexity of wastewaters, instability of H2 production, robust microorganisms, effect of membrane on two-chamber MEC, and integration of MEC with other treatment processes were deeply discussed. Except for the technical feasibility, both environmental feasibility and economic feasibility also need to meet social requirements. This review can indeed provide a basis for high-efficiency treatment and practical commercial applications of recalcitrant wastewaters via MECs in the future. Keywords: microbial electrolysis cells, complex wastewater, H2 production, renewable energy, energy efficiency DOI: 10.25165/j.ijabe.20191205.5061 Citation: Shen R X, Zhao L X, Lu J W, Watson J, Si B C, Chen X, et al. Treatment of recalcitrant wastewater and hydrogen production via microbial electrolysis cells. Int J Agric & Biol Eng, 2019; 12(5): 179–189.